2017
DOI: 10.1111/hae.13250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a product‐specific reference standard for the measurement of a PEGylated rFVIII activity: the Swiss Multicentre Field Study

Abstract: In this in vitro study, the type of reference standard had a major impact on the measurement of BAX 855 activity. Evaluation was more accurate and precise when using a product-specific reference standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…In a sample spiked with 3 IU/dL, however, the recovery of the same product reached a mean of 213.5% . Interestingly, during this study calibration of the assay with a product‐specific standard improved the recovery in the normal range, but not in the low range . A similar overestimation of low FVIII activity was observed in another multicentre study …”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In a sample spiked with 3 IU/dL, however, the recovery of the same product reached a mean of 213.5% . Interestingly, during this study calibration of the assay with a product‐specific standard improved the recovery in the normal range, but not in the low range . A similar overestimation of low FVIII activity was observed in another multicentre study …”
Section: Introductionsupporting
confidence: 75%
“…Similarly, in a multicentre study, Bulla et al recorded a mean recovery of 127.7% of the expected FVIII activity in a sample spiked with 80 IU/dL PEGylated rFVIII (Adynovate ® ). In a sample spiked with 3 IU/dL, however, the recovery of the same product reached a mean of 213.5% . Interestingly, during this study calibration of the assay with a product‐specific standard improved the recovery in the normal range, but not in the low range .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…43 A field study has been published in which 35 laboratories in 12 countries returned one-stage clotting FVIII assay data, and 11 centres in eight countries returned chromogenic assay results. 45 In contrast to the study of Turecek, this article reported that FVIII assays in spiked samples containing 30-80 IU/dL overestimated relative to the labelled potency by 28%-32% for one-stage assay and 69%-82% for chromogenic. Results of chromogenic assays and one-stage assays were on average 113% (range 101%-124% for the three samples) and 116% (range 92%-129%) of target based on stated potency, respectively.…”
Section: Adynovimentioning
confidence: 63%
“…FVIII activity is most commonly measured using the one‐stage aPTT assay. The one‐stage assay is simple but can be associated with significant reagent‐dependent variability due to the wide range of assay reagents (activator type, phospholipid composition), type of deficient plasma, calibrators and instrumentation . It has been reported that PEGylation can interfere with certain APTT reagents, in particular with some silica‐based reagents causing poor precision …”
Section: Introductionmentioning
confidence: 99%